Pendampingan Pelaksanaan Pekerjaan Saluran Irigasi Tersier Pada Kelompok Tani Desa Triwacu Wacu Kec. Kulisusu Barat Kab. Buton Utara - La Sianto; Erwin Hidayat; Saiful Bahri (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
During the dry season, the water requirements of the fields in Ambuau Indah Village cannot be met adequately, affecting farmer production. Based on this fact, this service is provided with the objective of analyzing irrigation network usage and planning tertiary irrigation channels on agricultural land in Triwacu Wacu Indah Village, Kec. West Kalisusu Kab. A more efficient North Buton is needed to alleviate water shortages in the village's rice fields and to increase the canal's effectiveness. Throughout the field measurements, the RT, RW, and group leaders asked participants to participate in a presentation on the steps necessary to complete this planning. The PkM team worked collaboratively with the community on socialization and training. The outcome of this planning is planned to be used by the Village Government and Village Residents to alleviate water shortages during the dry season, allowing them to carry out operations in the rice fields without having to consider the possibility of a water shortage. The result of this community activity is a drawing of the irrigation channel plan and budget plan, which will make irrigation work easier for the Village Government. Keywords: Planning, Tertiary Irrigation, Triwacu Wacu Village